MIKRONUTRIEN PENYEBAB ANEMIA PADA PENGGUNA NARKOBA DI MEDAN TEMBUNG[Micronutrient Causes of Anemia in the Drugs Users in Medan Tembung] - Ginta Siahaan; Roy Ferdi Siallagan; Rumida Purba; Riris Oppusungu (Media Gizi Indonesia, 2018)
Drug users are generally vulnerable to malnutrition because of the side effects of drugs itself that has resulted in appetite reduction and nutrients malabsorption. Inadequate nutrient intake especiallynutrient for haemoglobin synthesis is the main cause of anemia among drug users. The aim of this research was to analyze the relationship between intake of micronutrients and haemoglobin level among drug users in Medan Tembung Sub District.  This research was an observasional study with cross sectional design. The respondents was 73 drug users selected by snowball and accidental sampling technique. Datas were analyzed using the pearson correlation test and rank spearmean correlation followed by linier regression test to analyze the main variables which cause the anemia. There was a relationship between the intake of micronutrients such as iron (Fe), zinc (Zn), vitamin B9, vitamin B12 and vitamin C with the level of Hb where the value of p<0.05, while the Fe intake was the main cause of Hb depletion (r=0.661). It is needed to do socialization of health related side effects for using drugs which may impair the absorption and metabolism of micronutrients. Drug users should avoid the consumption of micronutrient inhibitor such as tea which effect to the low level of Hb.